Technological scouting as a tool for innovation commercialization - Ievsieiev, A. S. (WSEH, 2025)
Technological scouting is a strategic method for identifying and integrating external technological advances into innovation pipelines. By monitoring scientific progress, patents, and startup ecosystems, it reduces R&D uncertainty and accelerates commercialization. This process enables early recognition of disruptive technologies, supports partnerships and licensing, and aligns technological opportunities with market needs, thereby strengthening competitiveness and shortening time-to-market.
Keywords: technological scouting; innovation commercialization; emerging technologies; intellectual property; startup collaboration; strategic partnerships; time-to-market; innovation management